Defective platelet function in Niemann‐Pick disease type C1. Issue 1 (12th September 2020) - Chen, Oscar C. W.; Colaco, Alexandria; Davis, Lianne C.; Kiskin, Fedir N.; Farhat, Nicole Y.; Speak, Anneliese O.; Smith, David A.; Morris, Lauren; Eden, Emily; Tynan, Patricia; Churchill, Grant C.; Galione, Antony; et al.
Abstract: Niemann‐Pick disease type C (NPC) is a neurodegenerative lysosomal storage disorder caused by mutations in either NPC1 (95% of cases) or NPC2 . Reduced late endosome/lysosome calcium (Ca 2+ ) levels and the accumulation of unesterified cholesterol and sphingolipids within the late endocytic system characterize this disease. We previously reported impaired lysosome‐related organelle (LRO) function in Npc1 −/− Natural Killer cells; however, the potential contribution of impaired acid compartment Ca 2+ flux and LRO function in other cell types has not been determined. Here, we investigated LRO function in NPC1 disease platelets. We found elevated numbers of circulating platelets, impaired platelet aggregation and prolonged bleeding times in a murine model of NPC1 disease. Electron microscopy revealed abnormal ultrastructure in murine platelets, consistent with that seen in a U18666A (pharmacological inhibitor of NPC1) treated megakaryocyte cell line (MEG‐01) exhibiting lipid storage and acidic compartment Ca 2+ flux defects. Furthermore, platelets from NPC1 patients across different ages were found to cluster at the lower end of the normal range when platelet numbers were measured and had platelet volumes that were clustered at the top of the normal range. Taken together, these findings highlight the role of acid compartment Ca 2+ flux in the function of platelet LROs.